Design preferences for global scale: a mixed-methods study of “glocalization” of an animated, video-based health communication intervention - Adam, Maya; Chase, Rachel P.; McMahon-Rössle, Shannon A.; Kuhnert, Kira-Leigh; Johnston, Jamie; Ward, Victoria; Prober, Charles G.; Bärnighausen, Till (BMC public health, 2021)
Designing health communication interventions for global scaling promotes health literacy and facilitates rapid global health messaging. Limited literature explores preferences for animation prototypes and other content characteristics across participants in different global regions. Prior research underscores an urgent need for health communication interventions that are compelling and accessible across culturally and geographically diverse audiences. This study presents feedback from global learners on animation design preferences and other key considerations for the development of educational video content intended for global adaptation and scaling.